A secure storage scheme with key-updating in hybrid cloud. (2019) - Gao, Ge; Wu, Lei; Yan, Yunxue
As cloud computing continues to evolve, the role of hybrid cloud security becomes more and more important in the progress of cloud research. In order to improve the multi-user data sharing mechanism in hybrid cloud and enhance the security of hybrid cloud, this paper proposes a new security storage model of hybrid cloud, which combines the public cloud's cost savings and elasticity with the private cloud's security and customisation. In addition, by exploring the security of data storage and interoperability of the hybrid cloud, this paper adopts a forward-secure key-updating encryption scheme, so as to ensure the security of privacy data in hybrid clouds.